Loss of the Drosophila cell polarity regulator Scribbled promotes epithelial tissue overgrowth and cooperation with oncogenic Ras-Raf through impaired Hippo pathway signaling - Doggett, Karen (BioMed Central, 2011)
BACKGROUND: Epithelial neoplasias are associated with alterations in cell polarity and excessive cell proliferation, yet how these neoplastic properties are related to one another is still poorly understood. The study of Drosophila genes that function as neoplastic tumor suppressors by regulating both of these properties has significant potential to clarify this relationship. RESULTS: Here we show in Drosophila that loss of Scribbled (Scrib), a cell polarity regulator and neoplastic tumor suppressor, results in impaired Hippo pathway signaling in the epithelial tissues of both the eye and wing imaginal disc. scrib mutant tissue overgrowth, but not the loss of cell polarity, is dependent upon defective Hippo signaling and can be rescued by knockdown of either the TEAD/TEF family transcription factor Scalloped or the transcriptional coactivator Yorkie in the eye disc, or reducing levels of Yorkie in the wing disc. Furthermore, loss of Scrib sensitizes tissue to transformation by oncogenic Ras-Raf signaling, and Yorkie-Scalloped activity is required to promote this cooperative tumor overgrowth. The inhibition of Hippo signaling in scrib mutant eye disc clones is not dependent upon JNK activity, but can be significantly rescued by reducing aPKC kinase activity, and ectopic aPKC activity is sufficient to impair Hippo signaling in the eye disc, even when JNK signaling is blocked. In contrast, warts mutant overgrowth does not require aPKC activity. Moreover, reducing endogenous levels of aPKC or increasing Scrib or Lethal giant larvae levels does not promote increased Hippo signaling, suggesting that aPKC activity is not normally rate limiting for Hippo pathway activity. Epistasis experiments suggest that Hippo pathway inhibition in scrib mutants occurs, at least in part, downstream or in parallel to both the Expanded and Fat arms of Hippo pathway regulation. CONCLUSIONS: Loss of Scrib promotes Yorkie/Scalloped-dependent epithelial tissue overgrowth, and this is also important for driving cooperative tumor overgrowth with oncogenic Ras-Raf signaling. Whether this is also the case in human cancers now warrants investigation since the cell polarity function of Scrib and its capacity to restrain oncogene-mediated transformation, as well as the tissue growth control function of the Hippo pathway, are conserved in mammals.